Classical and novel GH receptor signaling pathways. (1st December 2020) - Frank, Stuart J.
Abstract: In this review, I summarize historical and recent features of the classical pathways activated by growth hormone (GH) through the cell surface GH receptor (GHR). GHR is a cytokine receptor superfamily member that signals by activating the non-receptor tyrosine kinase, JAK2, and members of the Src family kinases. Activation of the GHR engages STATs, PI3K, and ERK pathways, among others, and details of these now-classical pathways are presented. Modulating elements, including the SOCS proteins, phosphatases, and regulated GHR metalloproteolysis, are discussed. In addition, a novel physical and functional interaction of GHR with IGF-1R is summarized and discussed in terms of its mechanisms, consequences, and physiological and therapeutic implications.